Penentuan Waktu Baku dengan Stopwatch Time Study untuk Pengukuran Kerja Operator di PT XYZ Lampung Tengah - Wahyudi, Rizqi; Nugraha, Andhyka Tyaz; Kinasih, Anjas Sukma (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2023)
PT XYZ, a company in the agribusiness sector, operates a chick hatching production line that yields hatching eggs as its final product. Currently, the company's production process lacks standardized working hours across various crucial stations – namely, terminal, pullchick, vaccine, and packing stations. This absence of standardized hours poses a significant challenge, impacting labor productivity. Additionally, the work pace remains inconsistent among employees at these stations, resulting in unpredictable monthly fluctuations in hatching egg production, rendering it unstable. To address these challenges, the implementation of the stopwatch time study method becomes imperative. This research aims to ascertain cycle time, normal time, and establish standard working hours across the terminal, vaccine, pullchick, and packing stations. Furthermore, the goal is to standardize the work time specifically at pullchick and packing stations. The objective is to compare these standard times against the current practices to enhance worker productivity effectively. Following the research, notable improvements have been observed. The terminal station has experienced a 1-train increase in output, rising from the prior 18 trains to 19 trains. Similarly, the vaccine station has shown remarkable progress, with an output surge of 6 boxes per hour, escalating from a previous rate of 25 boxes/hour to 31 boxes/hour. These findings underline the positive impact of implementing standardized work times, indicating enhanced productivity and efficiency across these stations within PT XYZ's production process.